Proteomics approach reveals urinary markers for early pregnancy diagnosis in buffaloes - Codognoto, Viviane M. [UNESP]; de Souza, Fabiana F. [UNESP]; Cataldi, Thais R.; Labate, Carlos A.; de Camargo, Laíza S. [UNESP]; Esteves Trindade, Pedro H. [UNESP]; da Rosa Filho, Roberto R.; de Oliveira, Diego J.B. [UNESP]; Oba, Eunice [UNESP] (Elsevier, 2024)
This study aimed to compare urine proteomics from non- and pregnant buffaloes in order to identify potential biomarkers of early pregnancy. Forty-four females underwent hormonal ovulation synchronization and were randomly divided into two experimental groups: inseminated (n = 30) and non-inseminated (n = 14). The pregnant females were further divided into two groups: pregnant at Day 12 (P12; n = 8) and at Day 18 (P18; n = 8) post-ovulation. The non-pregnant group was also subdivided into two groups: non-pregnant at Day 12 (NP12; n = 7) and at Day 18 (NP18; n = 7). Urine was collected from all females on Days 12 or 18. The samples were processed for proteomics. A total of 798 proteins were reported in the urine considering all groups. The differential proteins play essential roles during pregnancy, acting in cellular transport and metabolism, endometrial remodeling, embryonic protection, and degradation of defective proteins. We suggest that some proteins from our study can be considered biomarkers for early pregnancy diagnosis, since they were increased in pregnant buffaloes. Significance: Macromolecules have been studied for early pregnancy diagnosis, aiming to increase reproductive efficiency in cattle and buffaloes. Direct methods such as rectal palpation and ultrasonography have been considered late. Thus, this study aimed to compare urine proteomics from non- and pregnant buffaloes to identify potential biomarkers of early pregnancy. The differential proteins found in our study play essential roles during pregnancy, acting in cellular transport and metabolism, endometrial remodeling, embryonic protection, and degradation of defective proteins. We suggest that these proteins can be considered possible biomarkers for early pregnancy diagnosis since they were increased in the pregnant buffaloes.
Keywords: Biomarkers; Buffaloes; Protein; Urine